Recent progress on PEDOT‐based wearable bioelectronics. Issue 5 (31st October 2022) - Zhang, Wanying; Su, Zhen; Zhang, Xianchao; Wang, Wentao; Li, Zaifang
Abstract: Bioelectronics, which can perform monitoring and biological signal collection of strain, pressure, and temperature at the same time, have attracted more and more attentions. To meet the unique requirements of wearable characteristics, the bioelectronic device with excellent flexibility is desired. At present, the biggest challenge for the flexible device is the candidate of electrode materials. The classical conducting polymer poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) has showed a promising potential in the field of wearable bioelectronic devices due to its high conductivity, excellent flexibility, aqueous processability, and good biocompatibility. Here, we reviewed the recent progress of PEDOT‐based wearable bioelectronic sensors and focus on the role of different PEDOT‐based flexible materials in addressing the mechanical strain, pressure, and temperature requirements. The impact of contemporary bioelectronic research will be highlighted. Abstract : Bioelectronics, which perform both monitoring and collecting biological signals (strain, pressure, and temperature), are attracting more and more attentions. This article aims to summarize the recent progress of various PEDOT‐based flexible materials in addressing the mechanical strain, pressure, and temperature requirements of wearable electronic sensors. This comprehensive review will help the community to systematically understand the design and application of PEDOT‐based flexible materials in bioelectronics.